Comprehensive Analysis of the Expression and Prognosis for Tripartite Motif-Containing Genes in Breast Cancer - Ning, Lvwen; Huo, Qin; Xie, Ni (Frontiers in Genetics, 2022)
Tripartite motif (TRIMs) with ubiquitin ligase’s function, play critical roles in antitumor immunity by activating tumor-specific immune responses and stimulating tumor proliferation, thus affecting patient outcomes. However, the expression pattern and prognostic values of TRIMs in breast cancer (BC) are not well clarified. In this study, several datasets and software were integrated to do a comprehensive analysis of the expression pattern in TRIMs and investigate their prognosis values in BC. We found TRIM59/46 were significantly upregulated while TRIM66/52-AS1/68/7/2/9/29 were decreased in BC and validated them using an independent cohort. The expressions of numerous TRIMs are significantly correlated with BC molecular subtypes, but not with tumor stages or patient age at diagnosis. Higher expressions of TRIM3/14/69/45 and lower expressions of TRIM68/2 were associated with better overall survival in BC using the Kaplan-Meier analysis. The multivariate Cox proportional hazards model identified TRIM45 as an independent prognostic marker. Further analysis of single-cell RNA-seq data reveals that most TRIMs are also expressed in non-tumor cells. Higher expression of some TRIMs in the immune or stromal cells, suggests an important role of TRIMs in the BC microenvironment. Functional enrichment of the co-expression genes indicates that they may be involved in muscle contraction and interferon-gamma signaling pathways. In brief, through the analysis, we provided several TRIMs that may contribute to the tumor progression and TRIM45 as a potential new prognostic biomarker for BC.